Comparison of Fast Inverse Square Root Algorithms for 3D Object Rendering using Ray Tracing - Filberto, Rico; Yolanda, Jacky; Agung Santoso Gunawan, Alexander (2022 2nd International Conference on Information Technology and Education (ICIT&E), 2022)
The purpose of this paper is to give an insight on the fast inverse square root that is used to compute the inverse square root of a floating-point number to normalize vector that is necessary in many computational problems such as lighting, reflection, and ray tracing. Giving an improvement of speed over 3 times the normal computation way, and an approximation with only 0.1 % error margin. This paper will be comparing several modifications of the algorithm that exist using ray tracing of a spherical object to see which is faster and more accurate through a 3D image rendering and table representation.